2020
DOI: 10.1111/jeb.13656
|View full text |Cite
|
Sign up to set email alerts
|

Selection on fruit traits is mediated by the interplay between frugivorous birds, fruit flies, parasitoid wasps and seed‐dispersing ants

Abstract: Every organism on Earth must cope with a multitude of species interactions both directly and indirectly throughout its life cycle. However, how selection from multiple species occupying different trophic levels affects diffuse mutualisms has received little attention. As a result, how a given species amalgamates the combined effects of selection from multiple mutualists and antagonists to enhance its own fitness remains little understood. We investigated how multispecies interactions (frugivorous birds, ants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…The sampling effort was sufficient to estimate all herbivore species, but rarefaction curves suggested that further sampling may be required for a complete assessment of parasitoid species associated with S. multijuga and I. vera (Figure 2). Further, we established the relationship between resources and insects by using path analysis, which is a powerful tool to assess direct and indirect connections in complex, tri‐trophic systems (Beduschi et al, 2015; Nascimento et al, 2015; Palacio et al, 2020). We found that the number of seeds per fruit was more important for both the abundance and richness of herbivores and parasitoids than the seed and fruit weight, which had a negative or nonsignificant relationship.…”
Section: Resultsmentioning
confidence: 99%
“…The sampling effort was sufficient to estimate all herbivore species, but rarefaction curves suggested that further sampling may be required for a complete assessment of parasitoid species associated with S. multijuga and I. vera (Figure 2). Further, we established the relationship between resources and insects by using path analysis, which is a powerful tool to assess direct and indirect connections in complex, tri‐trophic systems (Beduschi et al, 2015; Nascimento et al, 2015; Palacio et al, 2020). We found that the number of seeds per fruit was more important for both the abundance and richness of herbivores and parasitoids than the seed and fruit weight, which had a negative or nonsignificant relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Third, both components are inherently linked, as fruits enclose seeds and fruits must be pecked or swallowed before seeds can be dispersed, so the contribution of fruit removal to plant fitness is expected to be significant (Nakashizuka et al, 1995; Izhaki, 2002; Snell et al, 2019). This is most evident in the case of species with a fixed number of seeds per fruit, for which the number of fruits removed often scales linearly with the number of seeds dispersed (e.g., Sobral et al, 2013; Palacio et al, 2020). By contrast, seed removal is expected to be more decoupled from fruit removal in multi‐seeded species with a variable number of seeds per fruit (e.g., many species produce fruits that develop acropetally, where seed number per fruit changes drastically from bottom to top; Diggle, 1995) as the same number of fruits removed in two plants may lead to different numbers of seeds removed.…”
Section: Figurementioning
confidence: 99%
“…Additionally, variation in the disperser traits can also affect their responses to dispersal units' traits, since low and high-quality dispersers can differ in their foraging preferences (e.g. Russo 2003;Leal et al 2014b;Palacio et al 2020). Therefore, by influencing the dispersal units' traits, PL can indirectly affect the assemblage of dispersers interacting with the dispersal units and, consequently, the quality of seed dispersal received by pollen-limited plants.…”
Section: Indirect Effects Of Pollen Limitation On the Qualitative Com...mentioning
confidence: 99%